2003
DOI: 10.1590/s0034-70942003000600008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do halotano, isoflurano e sevoflurano sobre a função renal em cães sob pinçamento aórtico infra-renal

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
1
1
0
2
Order By: Relevance
“…In our study, blood pressure increase in the control group was mild (20%), but in expected levels when aortic cross-clamping is performed 3,7,15 , followed by increase in right atrium, pulmonary artery and pulmonary wedge pressures, cardiac and systolic indices, and right and left ventricle systolic work. Several authors have observed filling pressure increase during aortic cross-clamping 7, 15,16 , while others have not observed such changes 8 . In our study, hemodynamic response during aortic cross-clamping may be explained by blood volume redistribution.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…In our study, blood pressure increase in the control group was mild (20%), but in expected levels when aortic cross-clamping is performed 3,7,15 , followed by increase in right atrium, pulmonary artery and pulmonary wedge pressures, cardiac and systolic indices, and right and left ventricle systolic work. Several authors have observed filling pressure increase during aortic cross-clamping 7, 15,16 , while others have not observed such changes 8 . In our study, hemodynamic response during aortic cross-clamping may be explained by blood volume redistribution.…”
Section: Discussionsupporting
confidence: 44%
“…A hipertensão arterial é sempre a resposta cardiovascular mais freqüente durante o pinçamento aórtico, acompanhada por aumento das pressões de enchimento 3,7,15 . Na presente pesquisa, o aumento da pressão arterial no grupo controle foi de pequena proporção (20%), mas em níveis já esperados quando se realiza pinçamento aórtico infra-renal 3,7,15 , acompanhada por aumento das pressões do átrio direito, da arté-ria pulmonar e da artéria pulmonar ocluída, e também dos ín-dices cardíaco, sistólico e do trabalho sistólico dos ventrículos direito e esquerdo.…”
Section: Discussionunclassified
See 2 more Smart Citations